Third Smallest Wiener Polarity Index of Unicyclic Graphs - Fang, Wei; Ma, Muhan; Chen, FuYuan; Dong, Hufeng (Frontiers in Physics, 2020)
The Wiener polarity index WP(G) of a graph G is the number of unordered pairs of ver- tices u,v such that the distance between u and v is 3. In this paper, we determine the first three smallest Wiener polarity index of u- nicyclic graphs. Moreover, the corresponding extremal graphs are characterized.